Student Perspectives on the Relevance and Importance of Arts-Based Learning - Reingold, Matt (Journal of the Canadian Association for Curriculum Studies, 2018)
Drawing on interview data from a practitioner research study involving secondary students in a Jewish school, the following paper presents students’ explanations for why learning through the arts is a valuable and important classroom experience. The explanations offered by students reflected a strong self-awareness and understanding of their own learning styles and how the arts complimented their studies and challenged them in new ways. In addition to hearing how students appreciate learning through the arts, the data also suggests that teachers and other school stakeholders should find ways to provide opportunities for students to contribute to conversations about pedagogical practice.